Interplay of polymorphisms in sex hormone receptors and facial sexual differentiation in shaping prosocial behavior - Claudia Rodriguez-Ruiz; Denisa Cristina Lupu; Ana Belen Fernandez-Martinez; Miguel Pita; Enrique Turiegano (Scientific Reports)
Abstract Numerous studies have examined how morphological features showing sex differences relate to prosocial behaviors, often yielding contradictory results. However, these studies have never simultaneously considered the affinity of sex hormone receptors alongside variables such as sex-related facial morphology. In this study, we analyze their combined effect on behavior in three economic games: the prisoner’s dilemma, the dictator game, and the ultimatum game, as well as participants’ considerations regarding these games. Our results indicate that facial morphology and genetic polymorphisms in sex hormone receptors associated with hormone-binding affinity have an effect on prosocial behavior. These effects are often significant in women but not in men. When polymorphisms are included in the models, facial shape difference emerges as a relevant variable. Regarding hormone receptors, polymorphisms in the androgen receptor and β estrogen receptor genes, but not in the α estrogen receptor, show behavioral effects. Short androgen receptor alleles are associated with making larger offers and expecting less generosity. In women, greater facial differentiation shows similar effects, while larger β estrogen receptor alleles are linked to requiring higher offers. Overall, our findings point to the value of jointly considering receptor affinity and proxies for hormone exposure when exploring their relationship with prosocial behavior.